THE INFLUENCE OF TALENT MANAGEMENT, EMPLOYEE DEVELOPMENT AND EMPLOYEE MAINTENANCE ON EMPLOYEE PERFORMANCE IN PT. AINI SEJAHTERA - Rika Andriani Kombih; Nurmala; Yanita; Azhar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study is to determine how talent management, employee development, and retention programs of PT. Aini Sejahtera affect employee productivity. The importance of human resources in facilitating the achievement of organizational goals is what drives this study, especially in the competitive Bottled Drinking Water (AMDK) market. This study uses a quantitative survey-based technique. Using a saturated sampling approach, the population of this study consisted of 56 people who were all employees of PT. Aini Sejahtera. Data collection methods included conducting a survey with Likert scale questions. Multiple linear regression tests were used for data analysis. This study found that talent management, employee growth, and staff retention all contribute to better employee performance. The importance of an integrated approach to human resource management in improving individual and organizational performance is reinforced by these findings.